In vitro anti–Candida albicans activity of 100% peppermint (Mentha piperita) extract compared to 5% sodium hypochlorite in acrylic dentures - Guallpa Ochoa , Kevin Michael (2026)
Objective: To evaluate the in vitro anti-Candida albicans effect of 100% peppermint extract compared with 5% sodium hypochlorite on acrylic dental prostheses. Materials and Methods: This in vitro experimental analysis was carried out with 30 pieces of thermocured acrylic resin, 15 mm long x 15 mm thick, manufactured with attributes similar to those of a partially removable acrylic denture. The polymerization times and polishing procedures set by the manufacturer were strictly adhered to.  sample processing and analysis were perfomed at the Microbiology Laboratory of the Academic Health and Wellness Unit at the Azogues campus of the Catholic University of Cuenca. Results: Both the 100% peppermint extract and 5% sodium hypochlorite were shown to inhibit the growth of Candida albicans after 15 minutes of exposure. Conclusions:  The 100% peppermint extract and 5% sodium hypochlorite have antifungal activity in inhibiting the growth of Candida albicans on acrylic dental prostheses.